IMPACT DE LA TAXE STATIQUES D’EMBARQUEMENT DANS LES AVIONS SUR LES RECETTES NON FISCALES REALISEES PAR LA DIRECTION GENERALE DES RECETTES DU MANIEMA Cas de l’Aéroport de Kindu de 2016 à 2018 - Joseph ISEGE SHINDANO, (IJRDO - Journal of Business Management, 2021)
¶The social grogne observed with the Directorate-General of the Receipts of Maniema around the remuneration of its personnals and the suspicions of a bad management of the receipts, and especially those perceived regularly with the airport of Kindu under the heading `' Taxe statistics of loading on the aircraft '' caused in us curiosity to check if, during the period appointed for this study, those represent the most significant share of the total receipts generated by this financial control.¶ However, the results of this research showed that the share of the total receipts generated by the `' Taxe statistics of loading on the aircraft '' perceived with the airport of Kindu in the nontax receipts carried out overall by the DGRMA of 2016 to 2018 is about 3,49%;¶by far lower than that generated by the services of Mines and Economie which, during the three years retained for this study, respectively carried out 40% and 33,8% of the total nontax receipts recovered by the this provincial financial control with Kindu.